EFFECTIVENESS OF IMPLEMENTING JKN MOBILE APPLICATION ON ACCESSIBILITY OF HEALTH SERVICES AND ECONOMIC WELFARE IN SURABAYA - Amalia, Adhita; Samudra, Marcellina (Universitas 17 Agustus 1945 Surabaya, 2025)
The digitalization of the BPJS Kesehatan service system is increasingly advanced with the publication of the JKN Mobile Application. The JKN Mobile Application is an innovation carried out by BPJS Kesehatan in improving services to the community in the health sector, especially hospital patients, which is easy and practical. This study aims to analyze the effectiveness of the implementation of the National Health Insurance (JKN) mobile application in improving the accessibility of health services and the economic welfare of the community in Surabaya. This study uses a qualitative approach with a case study method. The results of the study show that the JKN mobile application provides convenience in accessing health service information, such as online registration, consultation schedules, and searching for the nearest health facilities. However, obstacles are still found, such as limited digital literacy in certain users and technical obstacles in the application that hinder the optimization of benefits. From an economic perspective, the use of the JKN application contributes to reducing transportation costs and waiting times, which ultimately has a positive impact on household financial efficiency. This study concludes that the JKN mobile application has significant potential to improve the accessibility of health services and the economic welfare of the community. However, improvements need to be made to the application features, digital education, and supporting infrastructure so that the benefits can be felt evenly. These findings are expected to be input for the government and application developers in optimizing digital-based health services in the future.